Design, Fabrication and Characterization of a Wideband Metamaterial Absorber for THz Imaging - Zeynab Alipour; Seyed Iman Mirzaei; Mehdi Fardmanesh (Engineering Proceedings)
In this paper, the design and optimization of a wideband THz metamaterial absorber (MMA) are proposed. By simulation, we reached four structures with absorptions higher than 50%, 70%, 80%, and 90%, with relative absorption bandwidths (RABWs) of 1.43, 1.29, 0.93, and 0.72, respectively. Terahertz absorbers can be used in many potential applications, such as in imaging, energy harvesting, scattering reduction, and thermal sensing. Our intended application was to use the optimal absorber on a thermal detector for detectivity over a wide THz range. Since broadband absorption in the range of 0.3 to 2 terahertz is considered for use in medical imaging, the MMA with more than 50% absorption in the range of 0.35-2.1 THz was selected. The designs were also intended to have the capability of being implemented on different devices, such as bolometers. The cost of the fabrication of the proposed absorber was also low because of the implementation of a single-layer MMA design and the utilization of affordable and more accessible materials and techniques. Our proposed structure had a minimum feature size of 3 μm, making the fabrication process convenient using the standard photolithography method as well. We used thin layers of nickel as the metal for both the single-layer pattern and ground layer, which were placed on the front and back sides of the structure, respectively. The nickel thin film layers were deposited using the sputtering technique and separated by a dielectric layer. The material chosen for the dielectric layer was SU8, which has proper electromagnetic properties and also good adhesion to nickel. Characterization of the fabricated absorber was performed using a terahertz spectroscopy system, and the experimental results verified the high absorption of the sample.